Proceedings of the 26th ACM Conference on Hypertext &Amp; Social Media - HT '15 2015
DOI: 10.1145/2700171.2791043
|View full text |Cite
|
Sign up to set email alerts
|

No Reciprocity in "Liking" Photos

Abstract: In social media, people often press a "Like" button to indicate their shared interest in a particular content or to acknowledge the user who posted the content. Such activities form relationships and networks among people, raising interesting questions about their unique characteristics and implications. However, little research has investigated such Likes as a main study focus. To address this lack of understanding, based on a theoretical framework, we present an analysis of the structural, influential, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Recent research in HCI has already shown some interest in social media and their features. The 'liking' behaviour of people on SNS, for example, has been investigated, noticing specific elements that influence the count of likes received [16]. With a focus on the social network Facebook, Wang et al found that people often feel regret about certain content that they have shared which ultimately caused them disadvantages in social and professional areas [35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in HCI has already shown some interest in social media and their features. The 'liking' behaviour of people on SNS, for example, has been investigated, noticing specific elements that influence the count of likes received [16]. With a focus on the social network Facebook, Wang et al found that people often feel regret about certain content that they have shared which ultimately caused them disadvantages in social and professional areas [35].…”
Section: Introductionmentioning
confidence: 99%
“… 10 The average number of Instagram posts in a sample of 20 million Instagram users (see Jang, Han, and Lee 2015). …”
mentioning
confidence: 99%
“…Consistent content is considered a basic rule for managing a successful Instagram account (Carroll, 2017). Jang et al (2015) also found empirical evidence that specialists on Instagram receive five times more Likes from the community than generalists who post a mix of content. And third, we included accounts with at least 15,000 followers, as a large number of followers guarantees that a wide range of users sees and potentially likes the images.…”
Section: Instagrammentioning
confidence: 85%
“…They can switch to the Instagram Explore section, where Instagram suggests content based on previous interactions, and where content can be searched based on keywords (i.e., hashtags). For a study of networks formed by follow and like activity on Instagram see also Jang, Han, and Lee (2015). Figure 1 shows what an Instagram post looks like.…”
Section: Instagrammentioning
confidence: 99%